Electronic medical record alert increases HIV screening rates: the Foch hospital pilot POP-up project - Alexandre Vallée; Dimi Sveltlane; Julie Trichereau; Stéphane Neveu; Erwan Fourn; Catherine Majerholc; Philippe Lesprit; Laurence Mazaux; Seheno Harijaona Henintsoa; Grazyna Matejczuk; Marc Vasse; David Zucman (BMC, 2022)
Abstract Background Despite significant national human immunodeficiency virus (HIV) screening activity, there are persistent delays in screening, and many missed diagnostic opportunities. To facilitate targeted screening, an electronic medical record (EMR) alert reminder was applied in the Foch hospital. Screening rates after implementation were reported. Methods A prospective cohort analysis was performed in Foch Hospital between 24 April 2018 and 4 October 2019 among hospitalized patients born in high HIV prevalence countries and/or having social vulnerability criteria (universal health coverage). From the admissions software, when specific low health coverage was provided and/or high-prevalence country of birth was registered, an electronic alert (EMR alert) appeared on the ward where the patient was hospitalized. The EMR alert database was examined for HIV screening and activity responses from each service of the Hospital. Results Eight thousand one hundred eighty-one alerts were recovered during the period for 1448 patients. 27 services used the EMR alert. Most of the alerts were directly closed (74.4%), 14.5% of the alerts were closed due to doctors declaring that they did not have time to respond. 297 (3.6%) of the 8181 alerts resulted in a prescription of HIV serology corresponding for 20.5% of the patients. Conclusion EMR alert can help to increase the rate of HIV screening in hospital care practice. Through this EMR alert system, HIV screening can be implemented as a common practice like any other medical alternative. Future research should examine the factors influencing physicians' attitudes to this alert system to improve the HIV screening rate.